1997
DOI: 10.1046/j.1365-3024.1997.d01-170.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to Lucilia cuprina in sheep selected for resistance or susceptibility to L. cuprina

Abstract: Sheep bred for resistance (R) or susceptibility (S) to fleece rot and myiasis (blowfly strike) have been shown to differ in inflammatory response to intradermal administration of blowfly (Lucilia cuprina) antigens and artificial challenge. The current paper describes analysis of antibody responses to L. cuprina antigens in the R and S animals. Serum antibody titres and specificities to larval antigens were examined and the specificity of wound exudate antibodies was also investigated in animals artificially ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…These humoral responses have been shown to be directed against E/S products of the larvae (42,43) and the salivary antigens (37) following natural infection, while the response has been characterized by the production of IgG (36,41) with subsequent analysis identifying a number of isotypes including IgG1, IgG2, IgA and IgM (44) and IgE (45) with the primary isotype being identified as IgG1 (42).…”
Section: Sheep Blowfly Infectionsmentioning
confidence: 99%
“…These humoral responses have been shown to be directed against E/S products of the larvae (42,43) and the salivary antigens (37) following natural infection, while the response has been characterized by the production of IgG (36,41) with subsequent analysis identifying a number of isotypes including IgG1, IgG2, IgA and IgM (44) and IgE (45) with the primary isotype being identified as IgG1 (42).…”
Section: Sheep Blowfly Infectionsmentioning
confidence: 99%
“…It has been determined that the immune system of a sheep can recognise the foreign components of a fly larva and produce an immune response to it [ 3 ], hence immune responses may play a role in defining flystrike resistance and susceptibility. However, using the Trangie research flocks in Australia, which were bred for resistance or susceptibility to fleece rot and flystrike, O’Meara et al [ 4 ] found that antibody titres did not differ between the resistant and the susceptible animals. This led them to suggest that the resistance of sheep to fleece rot and flystrike was likely to be founded in the innate immune response, and not the adaptive response.…”
Section: Introductionmentioning
confidence: 99%